1979
DOI: 10.1136/thx.34.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Diet, absorption, and hormone studies in relation to body weight in obstructive airways disease.

Abstract: Sixteen male patients with stable chronic obstructive airways disease were separated into two groups of eight according to arterial carbon dioxide tensions. Hypercapnia was associated with lower arterial oxygen tensions, higher red cell volume, and increased weight, while normocapnic subjects were decidedly thin. The considerable difference in body weight between the two groups could not be explained by variation in calorie intake, and malabsorption was excluded as a cause of weight loss in the underweight sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A dysfunctioning hypothalamic‐pituitary‐gonadal axis has been reported in COPD in previous studies (8–12). Moreover, a decreased response to administered gonadotrophin‐releasing hormone was detected in chronic airway diseases (13).…”
Section: Introductionmentioning
confidence: 61%
“…A dysfunctioning hypothalamic‐pituitary‐gonadal axis has been reported in COPD in previous studies (8–12). Moreover, a decreased response to administered gonadotrophin‐releasing hormone was detected in chronic airway diseases (13).…”
Section: Introductionmentioning
confidence: 61%
“…However, in diseases with chronic hypoxic manifestation, data are conflicting. In chronic obstructive pulmonary disease, fT 3 , fT 4 , and thyrotropin were not found to be altered in most studies [25][26][27]. Only one group found that severe airway obstruction is associated with reduced basal and stimulated thyrotropin levels [28].…”
Section: Discussionmentioning
confidence: 95%
“…Therapy with testosterone will always need to be carefully considered as there will always remain the potential for abuse by men wanting a cure for chronic fatigue and lack of energy or seeking their lost youth. Woolf et al, 1985Abnormal LH pulsatility Vogel et al, 1985Increased Wang et al, 1978a Semple et al, 1979Semple et al, , 1981 Lower in hypercapnic patients impaired response Oxygen may improve Aasebo et al, 1993 Asthma Lowered in prednisolone Elevated gonadotrophins Testosterone increased Reid et al, 1985Reid et al, , 1996 Gama et al, 1995 Epilepsy May be increased May be increased Toone et al, 1980, 1983 Reduced Increased Testosterone may Harper et al, 1972 improve bone mass Barreca et al, 1983Griggs et al, 1985a,b, 1989 Kennedy's syndrome Normal testosterone Increased Warner et al, 1992 DHT resistance…”
Section: Resultsmentioning
confidence: 99%
“…Patients with COAD have been found to have lower testosterone levels than controls. Serum LH and FSH were normal, and in view of the inappropriate gonadotrophin levels it was suggested that hypoxia led to pituitary suppression (Semple et al, 1979). Those patients who were also hypercapnic had significantly lower testosterone levels than those who were normocapnic.…”
Section: Respiratory Diseasementioning
confidence: 99%